PENERAPAN METODE PERMAINAN BERBURU UBUR-UBUR UNTUK MENINGKATKAN MINAT PESERTA DIDIK DALAM BELAJAR MATEMATIKA SISWA KELAS II SDN BLOTONGAN 02, SALATIGA - Rana Rizqina Gunadi; Antonius Wahyana (STKIP Subang, 2024)
This study aims to enhance interest in mathematics learning among second-grade students at SDN (State-Run Elementary School) Blotongan 02 Salatiga by implementing the